Blue spruce (Picea pungens) morphobiology and breeding prospects in domestic conditions - Norqulova; Firdavs Subxonberdiyev, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This article describes the process of sprouting blue spruce (Picea pungens) from seeds at home. The effects of soil fertility, temperature, humidity and light on plants are also covered. Photographs of the growing process are also provided.